Movimentos de fêmeas e filhotes de baleia-jubarte, Megaptera novaeangliae (Borowski, 1781), na área reprodutiva da costa brasileira - Mamede, Natália dos Santos (Universidade Federal de Juiz de Fora (UFJF), 2011)
The movement of animals is motivated by the need to carry out activities in certain habitat types in a specific time. Humpback whales, migrate to feeding grounds in summer to breeding grounds in winter. Its distribution is well known in the Brazilian coast, but the extent of his nurse area is not yet clear. Understand the relationship between physical environmental factors defining the niche of reproduction and parental care is important for effective planning of marine protected areas to encompass critical habitats. The telemetry from the satellite 41 females accompanied by calf were marked with transmitters (ARGOS), aiming to characterize the movements of females and calves on the Brazilian coast and correlate them with environmental variables. The average distance traveled was 1.005 km (± 29.97) with a maximum 56 and minimum distance 4.050 km. The couple female - calf focused on distances less than 150 km coastline and use mostly shallower water than 100m. The higher frequencies of locations are associated with larger buffers around coral reefs. The nurse area of humpback whales in the South Atlantic is related to coastal and shallow waters, being broader than the distribution of coral reefs. The choices of habitat use of females in breeding areas are a balance of energy expenditure between the drive and maternal care. The availability of environmental characteristics conducive to parental care is rarely evaluated and may result in partial interpretations of the phenomena of distribution and use of space in cetaceans. O movimento dos animais é motivado pela necessidade de executar atividades em certos tipos de habitat em um tempo específico. As baleias-jubarte migram de áreas de alimentação, no verão, para áreas reprodutivas, no inverno. Sua distribuição é bem conhecida na costa brasileira, mas, a extensão de sua área de cria ainda não é clara. Compreender as relações entre fatores físicos ambientais, definindo o nicho de reprodução, e o cuidado parental é importante para efetivar planejamentos de Áreas ...